PRELIMINARY STUDY ON THE BIOLOGY AND FISHERY OF MURAENESOX TALABONOIDES (BLEEKER) FROM BOMBAY AND SAURASHTRA WATERS - Kagwade, P V (Indian Journal of Fisheries, 2011)
Muraenesox talabonoides, a false conger eel ('wam'), supports an important fisheryalong the north-western parts of India. It is a predator, taking in a variety of fishes,including eels, and prawns. Length frequency studies showed that recruitment of smalljuveniles of the species to the trawl fishery is twice a year. The size at first maturity is125 cmt There appeared to be two spawning periods, one in April-May and the other inSeptember-October. A specimen of 169 cm total length was estimated to have afecundity of 922,033 ova. The fishery is mainly dependent on the trawling operationandastudy of the New India Fisheries Company's'vessel landings during 1956-63 showedthat 'wam' formed over 10% of the trawl catches and that the southern part of Bombay—Saurashtra waters, comprising Cambay, Veraval and Bombay formed the more productivegrounds. The eels were found to move to the deeper zone in the warmer monthsfrom April onwards, and move towards the shallower area by September and then moveto moderately deep waters up to March.